Response of Content Creators Towards Kreator Pass as a Learning Media - Nicholas Nicholas; Bayu Syahputra; Jimmy Pratama (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
As time goes, humans kept on finding new ways to make their everyday job easier. New technologies are invented and plays an important role in the modern era. One of the example of technologies are internet, to make transactions easier. New job opportunities involving technology are created, such as content creator. They are individuals or companies who create contents on the internet, specially social media. As time goes, more content creators shows up. Kreator Pass is a startup that help content creators compete in the market. This article is to decide whether kreator pass can be useful or not for content creators.